Implementasi Model Sequenced Dalam Pembelajaran Tematik Terpadu Di SD - yusrani fitri; Yanti Fitria; Yeni Erita; Rina Marlina; Fadhilah (Program Studi Pendidikan Guru Sekolah Dasar, Universitas Muhammadiyah Sukabumi, 2023)
Thematic learning in elementary schools aims to improve and improve the quality of education. The implementation of integrated thematic learning encounters various problems such as low student interest and attention, unattractive learning and teacher's lack of understanding of appropriate and varied learning models in the learning process. One learning model that can be used as a solution to overcome this problem is the sequenced learning model. The method used in this research is literature research (library research). The implementation of the sequenced learning model in various studies shows that there is a significant increase in student learning outcomes. The application of the sequenced model is oriented in a way that several topics from a subject are combined and sequenced so that they are connected to one another, this certainly makes learning more interesting and increases student enthusiasm in the learning process. An understanding of the sequenced learning model must be understood by every teacher because it is a one of the reference learning models in integrated thematic learning